Chapter Evolución de los criterios ecdóticos en las ediciones modernas del teatro de Shakespeare - Tronch Pérez, Jesús (Studi e saggi, 2021)
Editorial criteria in critical editions of Shakespeare’s plays have evolved from a 18th-century arbitrary eclecticism into one restricted by the editor’s knowledge of the nature and transmission of the early texts, a knowledge developed by the 20th-century New Bibliography that specially informs paleographical and bibliographical criteria. Roughly from the 21st century, these criteria have evolved into a conservatism influenced by a social view of texts, which stands on a par with the primordial criterion of reconstructing the text intended by the author. This textualism is nourished by a skepticism about the certainty the New Bibliography inspired in what editors know about the texts’ transmission.